Improving Critical Thinking Skills Based on Neuroscience in Islamic Education Learning - Hasanah, Uswatun; Saputri, Yolanda Amelia; Yusnita, Erni; Hidayah, Nur; Velina, Yessy (Faculty of Tarbiyah Universitas Islam Tribakti Lirboyo Kediri, 2024)
Students' critical thinking has been a significant concern within education development efforts, and this needs to be addressed and promoted by teachers. However, most teachers barely promote this skill, especially related to Islamic education, which leads to more challenges for students in learning Islam. Therefore, encouraging innovation and strategies to develop students' critical thinking in learning Islam is necessary. This research aims to analyze the implementation of the neuroscientific approach and how it can develop students' critical thinking skills. This research used a Quasi-Experimental method with a pretest-posttest design. Eighth-grade students at SMPN 1 Talangpadang Tanggamus were the population of this research. Only two classes, Class VIII.1 (experimental class) and Class VIII.3 (control class) were used as the research sample chosen using simple random sampling. The result of the research showed that the neuroscientific approach has a significant influence on improving students' critical thinking skills. However, the degree of the influence was varied across the data. Moreover, this research also showed that the implementation of the neuroscientific approach in learning should be explored and expanded to promote students' critical thinking skills.